Sheet Jam Formulation from a Mix of Seaweed and Pineapple Fruit - Gustin H Ismail; Nikmawatisusanti Yusuf; Lukman Mile (The NIKe Journal, 2019)
The aim of this study was to obtain a formula of sheet jam from a mixture of K. alvarezii seaweed and the best pineapple based on organoleptic hedonic sheet jam test. The results of preliminary research for cooking time based on trial and error is 60 minutes so that jam can be made in sheet form. The main research results on the characteristics of a mixture of jam sheets between seaweed and pineapple fruit concluded that the chosen formula was sheet jam with a comparison of seaweed and pineapple material of 1: 2. Keywords: Sheet jam; K. Alvarezii; pineapple; organoleptic